2021
DOI: 10.21037/tcr-21-1545
|View full text |Cite
|
Sign up to set email alerts
|

Patient outcomes after non-curative endoscopic submucosal dissection for early colorectal cancer: a single-center, retrospective cohort study

Abstract: Background: The treatment patterns and outcomes for patients after non-curative endoscopic submucosal dissection (ESD) remain controversial, particularly among those requiring preservation of the anal sphincter or advanced age. This retrospective study aimed to investigate the treatment patterns and outcomes in patients after non-curative ESD for early colorectal cancer (CRC). Methods: This was a retrospective review in Chinese patients who received non-curative ESD for early CRC, and who were treated in the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Moreover, the survival impact of additional surgical intervention has been reported to be limited even in patients with high-risk T1 tumors in several studies, although those studies were retrospective in design and had relatively small numbers of patients. 14,21,22 Thus, the true impact of additional surgery, especially in patients at high surgical risk, still remains a topic of debate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the survival impact of additional surgical intervention has been reported to be limited even in patients with high-risk T1 tumors in several studies, although those studies were retrospective in design and had relatively small numbers of patients. 14,21,22 Thus, the true impact of additional surgery, especially in patients at high surgical risk, still remains a topic of debate.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence rates of lymph node metastasis, however, are reported to be around 10.3% to 14.0% based on this background, 14,22,25 suggesting that many patients end up undergoing unnecessary invasive procedures. Moreover, the survival impact of additional surgical intervention has been reported to be limited even in patients with high-risk T1 tumors in several studies, although those studies were retrospective in design and had relatively small numbers of patients 14,21,22 . Thus, the true impact of additional surgery, especially in patients at high surgical risk, still remains a topic of debate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although recent studies reported that salvage ESD for local/recurrent colorectal tumors is effective and safe, most of the tumors included in this study were resected using the endoscopic mucosal resection (EMR) method, and most of the procedure was performed by experts in large volume centers 7 . For patients with non-curative resected T1 CRC, there is still controversy whether additional surgery is necessary or if surveillance alone is sufficient 8 . Although current guidelines recommend surgery, residual tumor was found in less than 7–18% of patients in previous studies 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%